Project Portfolio Management in Engineering: Strategies for Resource Optimization and Risk Balancing - Omidi, Soheila (Management Strategies and Engineering Sciences, 2020)
Project Portfolio Management (PPM) plays a critical role in the successful execution of engineering projects, which are often characterized by high complexity, significant resource demands, and substantial risks. This narrative review provides a comprehensive analysis of strategies for resource optimization and risk balancing within the context of PPM in engineering. The review synthesizes findings from a broad range of studies, highlighting the importance of advanced tools, methodologies, and technologies in optimizing resource allocation and managing risks across engineering project portfolios. Key strategies discussed include the use of decision-support systems, lean management principles, and digital technologies for resource optimization, as well as risk assessment frameworks and mitigation techniques for effective risk management. The review also emphasizes the importance of integrating resource optimization and risk management strategies to enhance project outcomes and align portfolios with organizational objectives. The findings offer valuable insights for both researchers and practitioners in the field of engineering PPM, identifying best practices and suggesting directions for future research, particularly in the context of emerging technologies.